Self-Transforming Powers - Elisa Paganini (Metaphysics)
I investigate the hitherto unexplored hypothesis that powers may be ontically vague, and offer an account of what powers would be like in such a case. The proposed account offers an innovative characterisation of powers as forces that transform themselves into their manifestations. It builds on, but also critiques, Neil E. Williams’s (2019) recent theory of powers. I conclude by considering the general implications of my proposal for the metaphysics of causality.